Implementation of tax planning to achieve VAT efficiency at PT. Crayon Work - Mawardani, Devian Prima; Wintro Siringoringo, Whereson Helpme (JAAF (Journal of Applied Accounting and Finance), 2025)
This study aims to analyse the tax planning case at PT Crayon Work. The strategy taken by an individual or company to manage its tax obligations in a way that is appropriate with tax regulations is called tax planning. Companies do ways to save taxes, one of which is by planning taxes on Value Added Tax (VAT). The problem that occurs at PT Crayon Work is that there is no tax planning implemented. This study aims to analyse (Tax Planning) in PT. Crayon Work in the context of the efficiency of paying VAT. Qualitative descriptive method used in this study, in which the researcher describes and describes the object being studied through data and information that has been collected for analysis. The results of this study that PT. Crayon Work can minimize VAT payable in 2020 through tax planning for the purchase of BKP/JKP with VAT, from IDR 305,922,082 to IDR 279,065,803, or a decrease of 8.78%. PT Crayon Work purchases BKP/JKP only to PKPs that have been confirmed. Updating tax planning regularly is an important step taken by the company.